High levels of PF4, VEGF-A, and classical monocytes correlate with the platelets count and inflammation during active tuberculosis - Urbán-Solano, Alexia; Flores-Gonzalez, Julio; Cruz-Lagunas, Alfredo; Pérez-Rubio, Gloria; Buendia-Roldan, Ivette; Ramón-Luing, Lucero A.; Chavez-Galan, Leslie (Frontiers in Immunology, 2022)
Platelets play a major role in coagulation and hemostasis; evidence supports the hypothesis that they also contribute to immunological processes. Increased platelet count has been associated with poor prognosis during tuberculosis (TB). Platelet-monocyte aggregates have been reported in patients with TB, but it is still unclear if only one monocyte subpopulation is correlated to the platelet count; moreover, the platelet-monocyte axis has not been studied during latent tuberculosis (LTB). In this study, mononuclear cells and plasma were obtained from patients diagnosed with active drug-sensitive TB (DS-TB, n=10) and LTB (n=10); cytokines and growth factors levels associated to platelets were evaluated, and correlations with monocyte subpopulations were performed to identify a relationship between them, as well as an association with the degree of lung damage. Our data showed that, compared to LTB, DS-TB patients had an increased frequency of platelets, monocytes, and neutrophils. Although DS-TB patients showed no significant difference in the frequency of classical and non-classical monocytes, the classical monocytes had increased CD14 intensity of expression and frequency of TLR-2+. Furthermore, the plasma levels of angiogenic factors such as Vascular endothelial growth factor (VEGF-A), Platelet-derived growth factor (PDGF-BB), and Platelet factor-4 (PF4), and pro-inflammatory cytokines like Interleukin 6 (IL-6), Interleukin 1 beta (IL-1β), and Interferon-γ-Inducible Protein 10 (IP-10) were increased in DS-TB patients. In addition, PF-4 and VEGF-A correlated positively with the frequency of classical monocytes and the platelet count. Using a principal component analysis, we identified four groups of DS-TB patients according to their levels of pro-inflammatory cytokines, angiogenic factors, and degree of lung damage. This study establishes that there is a correlation between VEGF-A and PF4 with platelets and classical monocytes during active TB, suggesting that those cell subpopulations are the major contributors of these molecules and together, they control the severity of lung damage by amplification of inflammatory environment.